Effect of super-ambient conditions on the upper explosion limit of ethane/oxygen and ethylene/oxygen mixtures. (May 2019) - Yu, Xiaozhe; Yan, Xingqing; Ji, Wentao; Luo, Can; Yao, Futong; Yu, Jianliang
Abstract: The upper explosion limit (UEL) of ethane/oxygen and ethylene/oxygen at elevated pressures up to 2.6 MPa and temperatures up to 543.15 K were measured. A coiled nichrome hotwire placed at the center of the vessel was used as the ignition source. Explosion is said to have taken place if there is a pressure rise of at least 5% of the initial pressure in the vessel after ignition. Experimental data obtained in the 1.5 L cylinder and the 20 L sphere had a difference less than 0.5%. Results showed that the test data obtained in the 1.5 L cylinder were reliable (with the relative standard deviation less than 0.15%), and can be used for industrial applications. Leveling off curves of UEL in oxygen depended on temperature and linear (logarithmic) relationships depended on pressure were shown. The transition pressures of 1.6 MPa (ethane/oxygen) and 1.0 MPa (ethylene/oxygen) which made the slope (increasing rate) of UEL curves change from pressure-sensitive to temperature-sensitive were found. Algebraic equations were established for assessing the data of UEL of ethane/ethylene in oxygen at elevated conditions straightforward. Highlights: The UEL of ethane/oxygen and ethylene/oxygen at elevated pressures and temperatures were measured. Functions fit for the UEL in oxygen at elevated pressures and temperatures were established. Experimental data obtained by using 1.5 L cylinder and 20 L sphere were compared.